PENGARUH BRAND IMAGE DAN INFLUENCER ENDORSEMENT TERHADAP PURCHASE INTENTION PADA SMARTPHONE SAMSUNG DENGAN TRUST SEBAGAI VARIABEL MEDIASI - Bintang Julian Pratama; Ahmad Mardalis (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the influence of Brand Image and Influencer Endorsement on Purchase Intention on Samsung smartphones with Trust as a mediation variable. This research method is quantitative. The population in this study is all consumers or users of Samsung smartphones. The total sample of this study was 286 respondents. The sampling technique uses a non-probability sampling approach with purposive sampling techniques. The type of data used in this study is primary data. Data collection techniques using questionnaires and research instruments. The data analysis technique in this study uses a Partial Least Square (PLS)-based SEM structural equation model. The result of this study is that Brand image has a positive and significant influence on Purchase Intention. Influencer endorsements have a positive but not significant influence on Purchase Intention. Brand image has a positive and significant influence on trust. Influencer endorsements have a positive and significant influence on Trust. Trust has a positive and significant influence on Purchase Intention. Brand image has a positive and significant influence on purchase intention mediated by Trust. Influencer endorsements have a positive and significant influence on trust-mediated purchase intent